The Lost Orchard : The Palestinian-Arab Citrus Industry, 1850-1950 - Kabahā, Muṣṭafá; Karlinsky, Nahum (Book collections on Project MUSE., 2021)
"This book portrays the unknown history of the "Lost Orchard" of pre-Nakba Palestinian-Arab society, of the people who constituted its social fabric and of the special, amicable, bi-national and consociational relations it established with its Zionist-Jewish counterpart"--